Development of pathological skin models: from conventional techniques to 3D bioprinting - Rielland, Maïté; Bernerd, Françoise; Camman, Marie; Tan, Xuezhu; Seyler, Nathalie (Frontiers in Bioengineering and Biotechnology, 2025)
Reconstructed human skin models were first developed in the 1970s. Since then, they have played a pivotal role in dermatological research, significantly advanced our understanding of skin biology, and brought huge insights into dermatological pathologies. Many conventional pathological skin models exist covering a wide range of diseases including melanomas, psoriasis, atopic dermatitis, genetic disorders, and wound healing conditions. However, conventional skin models remain limited by technical constraints which prevent complete replication of the spatial organization (heterogeneities, microenvironment) of skin diseases. Bioprinting has emerged as a powerful technology with the potential to overcome some of these limitations. By enabling precise control over the spatial organization of multiple cell types within a tailored extracellular matrix, bioprinting facilitates the creation of complex, three-dimensional skin models that closely mimic the architecture and function of human skin. This review initially explores the current landscape of conventional reconstructed pathological skin models. Bioprinting techniques, bioink considerations, and their roles in creating complex skin models are discussed. It then highlights the benefits of bioprinting for tissue microenvironment replication, architectural fidelity, and integration of multiple cell types in pathological skin models. In terms of healthy skin models, three-dimensional bioprinting is already revolutionizing personalized medicine, automating model production, and supporting translational research and therapeutic and cosmetic screening. It also represents a transformative approach for developing advanced pathological skin models despite the remaining technical and regulatory challenges.